2021
DOI: 10.1186/s12889-021-11818-1
|View full text |Cite
|
Sign up to set email alerts
|

Young people’s romantic relationships and sexual activity before and during the COVID-19 pandemic

Abstract: Background Social distancing measures to reduce the spread of COVID-19 may profoundly impact young people’s relationships. This study compared adolescent and young adults’ romantic relationships and sexual activity before and after social distancing policies were enacted. Methods In June 2020, 351 youth participating in an ongoing intervention study in Fresno County, California completed an online survey about their experiences related to COVID-19.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…Although not all studies have demonstrated that social distancing during the pandemic resulted in less sexual interaction among adults [ 25 ], a significant number of studies from different countries have shown a decrease in partnered sex and increased online dating during the pandemic [ 26 29 ]. Similar results were demonstrated in studies on adolescents and young adults, who turned to digital forms of communication with partners and to digital pornography use during the pandemic [ 23 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although not all studies have demonstrated that social distancing during the pandemic resulted in less sexual interaction among adults [ 25 ], a significant number of studies from different countries have shown a decrease in partnered sex and increased online dating during the pandemic [ 26 29 ]. Similar results were demonstrated in studies on adolescents and young adults, who turned to digital forms of communication with partners and to digital pornography use during the pandemic [ 23 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…While the study harnesses the infrastructure of multiple research studies and collaboration to better understand contextual factors of COVID-19 in this single urban community with high STI prevalence and COVID-19 health disparities, there is a small sample size and limited generalizability to other communities or youth not involved in sexual health research. Like other recent studies, much of these data are regionally specific and leveraged youth already in research studies due to the limited access to youth during the pandemic [ 21 , 22 ]. The present study further adds to our knowledge about youth sexual behavior during COVID-19 and suggests that factors aside from the impacts of COVID-19 on social circles influence the sexual health of AYA.…”
Section: Discussionmentioning
confidence: 99%
“… 2021a ; Both, Castle, and Hensen 2021 ; Yarger et al. 2021 ; Endler et al. 2021 ; Balachandren et al.…”
Section: Discussionmentioning
confidence: 99%
“…Since the COVID-19 pandemic began, commentaries (Hussein 2020;Aly et al 2020;Kumar, Malviya, and Sharma 2020;Hall et al 2020) and empirical studies on the impacts of COVID-19 on SRH have emerged (Gilbert et al 2021;Bolarinwa 2021;Lewis et al 2021a;Both, Castle, and Hensen 2021;Yarger et al 2021;Endler et al 2021;Balachandren et al 2022;Steiner et al 2021). Some studies, such as ours, found that access to contraception became difficult during lockdowns (Balachandren et al 2022), and others focused specifically on the impact on adolescents and young people (Lewis et al 2021a;Both, Castle, and Hensen 2021;Yarger et al 2021;Steiner et al 2021). Two of these studies have shown findings that support our findings (Both, Castle, and Hensen 2021;Lewis et al 2021b).…”
Section: Discussionmentioning
confidence: 99%